Penerapan Game Edukasi untuk Mengenal Tokoh Pemimpin Bangsa Indonesia pada Siswa Kelas III SDN 003 Bangun Jaya Tambusai Utara - Chandra, Detri Amelia (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
This research aims to implement the educational game "Guess Who I Am" with the theme "Leaders of Indonesia" in the third-grade class of SDN 003 Bangun Jaya Tambusai Utara to enhance students' understanding of the nation's leaders. The research methodology combines quantitative and qualitative approaches, utilizing data collection through observation, quiz analysis, and interviews. The results indicate a significant improvement in students' interest, motivation, and understanding of historical content, along with the development of logical and social skills. The implication is that the use of educational games can be an effective strategy to enhance history learning at the elementary level, providing a positive boost to student interest and stimulating the development of cognitive and social skills.Keywords: Application, Educational Games, Learning, National Leaders